2007
DOI: 10.1007/978-1-59745-529-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Connectivity in Engineered Neuronal Networks

Abstract: In this study, we have demonstrated a method to organize cells in dissociated cultures using engineered chemical clues on the culture surface and determined their connectivity patterns. Although almost all elements of the synaptic transmission machinery between neurons or between neurons and muscle fibers can be studied separately in single-cell models in dissociated cultures, the difficulty of clarifying the complex interactions between these elements makes random cultures not particularly suitable for specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…1A). The normalized area values of N1s (401 and 399 eV) to the Si 2p 3/2 peaks were stable throughout the study at 1300–2300 and were similar to previously published results [38,39,43,58,59]. Static contact angle measurements (Fig.…”
Section: Resultssupporting
confidence: 90%
“…1A). The normalized area values of N1s (401 and 399 eV) to the Si 2p 3/2 peaks were stable throughout the study at 1300–2300 and were similar to previously published results [38,39,43,58,59]. Static contact angle measurements (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The patterns consisted of two circular regions ͑20 m diameter͒ intended for adhesion of the cell bodies. 2 m lines that extend in an arc from one somal adhesion site to another connected these circular regions, similar to Ravenscroft et al 16 and Molnar et al 29 The dashed lines extending radially from the somal adhesion sites further surrounded the somal adhesion sites. This geometry served to induce a specific polarity in the neurons similar to Stenger et al, 13 such that they would extend a dominant process ͑which would ultimately become the axon͒, and contact the soma of the opposing cell.…”
Section: Cell Culturesupporting
confidence: 68%
“…6͑e͒ is a pattern designed specifically for creating two-cell networks of hippocampal neurons. 29 The metallization results confirmed that patterns fabricated from the combination of PEGSi and DETA engineer high contrast patterns that were suitable for cell culture. Since the copper reduction reaction only occurs on regions containing the amine-terminated DETA, it can be seen that the DETA was confined primarily to regions where the PEGSi had been ablated.…”
Section: Metallizationsupporting
confidence: 54%
“…Our laboratory routinely uses SAMs to modify and pattern glass coverslips for cell culture applications[15, 16, 3032, 42]. However, patterning cardiac myocytes on MEAs presented a challenge for three primary reasons: 1) The complex composition of the MEA surface made the verification of the surface modification step difficult, 2) MEAs are expensive, thus methods needed to be developed that enabled them to be cleaned and refunctionalized for repeated use and 3) patterned cardiac myocytes do not grow optimally on the standard trimethoxysilylpropyldiethylenetriamine (DETA) surfaces[15] nor on clean glass.…”
Section: Resultsmentioning
confidence: 99%